UPAYA PEMAHAMAN PEMBUPAYA PEMAHAMAN PEMBELAJARAN DARING SISWA SMP KELAS VII PADA MATERI SEGIEMPATELAJARAN DARING SISWA SMP KELAS VII PADA MATERI SEGIEMPAT - Reni Nur Afifah; M. Afrilianto (IKIP Siliwangi, 2021)
The purpose of this study is a type of classroom action research that aims to determine the mathematical understanding ability of junior high school students on quadrilateral material. The population in this study were all students of class VII-A in SMP Kec. Cihampelas involving 30 students. This type of research is classified as classroom action research, which consist of 2 (cycles) namely cycle I and cycle II. The implementation of cycles I and II were carried out in 2 meetings each, the number of meetings in this class action research was 6 meetings, the first meeting was used for pretest, 2-3 meetings were used for online learning in the first cycle, 4-5 meetings were used meetings were used for online learning cycle secound, and the 6 meetings conducted a post-tes to review student learning outcomes online. The instruments used in date collection were pretest, posttest and observation sheets. Techiniques in data processing using descriptive tables in the form of averages and percentages. The research acts as the implementation of online learning and the teacher as the observator in the whatsapp group. In the next stage, teacher and student observation sheets were given to review the results. The results of this study indicate that: (1) There is an increase in student learning outcomes as indicated by an increase in the first cyle of the average value of 60.00 with a percentage of 46.67% and the second cycle the averege value achieved is 80.21 with a percentage of 83,33%, (2) The activities of teachers and students in online learning are quite good from each cycle, but there must be some things that must be improved, namely the response of students to activeness in the whatsapp group during online learning.